Temporally enhanced RSEI and nighttime lights reveal long-term ecological changes and effective protection in China’s inaugural national parks - Chunhui Wen; Tengfei Long; Guojin He; Weili Jiao; Wei Jiang (Ecological Indicators)
Protected areas are vital for preserving biodiversity and ensuring ecosystem services. Rational assessments of long-term change in ecological environment quality within these areas are crucial for informing effective conservation strategies and policy decisions. This study addresses the challenges of long-term ecological monitoring by improving the Remote Sensing Ecological Index (RSEI) to analyze spatiotemporal changes in ecological quality of China’s inaugural national parks (NPs) from 2000 to 2022. It also examines changes in human activities within and surrounding these parks using nighttime light (NTL) remote sensing data. We used Sen + MK trend analysis, climate factor removal analysis, and geographical detectors to explore the driving forces behind ecological environment quality changes and compare the effectiveness of ecological protection measures across different NPs. The results indicate that: 1) The temporally enhanced RSEI (tRSEI) effectively integrates the dynamic changes of multiple variables and offers better temporal comparability for long-term ecological monitoring; 2) From 2000 to 2022, the ecological environment quality within the inaugural NPs significantly improved, with more noticeable improvements observed following the implementation of pilot conservation programs; 3) The spatial variation in ecological quality within these NPs is driven by the interaction of multiple factors, including human activities, climate variability, and topographical conditions, with significant differences among the parks; 4) Although overall NTL intensity both inside and outside the NPs increased between 2000 and 2022, especially with accelerated growth in surrounding areas post-pilot program implementation, NTL levels within the parks remained relatively low. Interestingly, a significant positive correlation between tRSEI and NTL changes was observed in Giant Panda and Hainan Tropical Rainforest NPs, suggesting that the increase in NTL did not negatively impact the ecological environment within these protected areas. This study provides recommendations for ecological protection and management in different NPs, offering insights for the effective management of protected areas in China and globally.